2000
DOI: 10.1091/mbc.11.5.1709
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Cdc42, Rac, PAK, and Rho-Kinase in Response to Hepatocyte Growth Factor Differentially Regulates Epithelial Cell Colony Spreading and Dissociation

Abstract: Hepatocyte growth factor (HGF), the ligand for the Met receptor tyrosine kinase, is a potent modulator of epithelial-mesenchymal transition and dispersal of epithelial cells, processes that play crucial roles in tumor development, invasion, and metastasis. Little is known about the Met-dependent proximal signals that regulate these events. We show that HGF stimulation of epithelial cells leads to activation of the Rho GTPases, Cdc42 and Rac, concomitant with the formation of filopodia and lamellipodia. Notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
213
3
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(237 citation statements)
references
References 74 publications
(129 reference statements)
20
213
3
1
Order By: Relevance
“…Moreover, some of the signaling pathways used by HGF/Met to induce scattering have been delineated in these cells (Ponzetto et al, 1994;Ridley et al, 1995;Royal et al, 2000;Zondag et al, 2000). To confirm the growth factor dependence of p120-induced cell migration observed in keratinocytes ( Figure 1C), and to dissect the biochemical steps downstream of p120, we introduced p120 and ⌬N-p120 into MDCK cells by either adenoviral infection or transfection and isolation of cell clones.…”
Section: Expression Of ⌬N-p120 In Mdck Cells Prevents Hgf-induced Motmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, some of the signaling pathways used by HGF/Met to induce scattering have been delineated in these cells (Ponzetto et al, 1994;Ridley et al, 1995;Royal et al, 2000;Zondag et al, 2000). To confirm the growth factor dependence of p120-induced cell migration observed in keratinocytes ( Figure 1C), and to dissect the biochemical steps downstream of p120, we introduced p120 and ⌬N-p120 into MDCK cells by either adenoviral infection or transfection and isolation of cell clones.…”
Section: Expression Of ⌬N-p120 In Mdck Cells Prevents Hgf-induced Motmentioning
confidence: 96%
“…It was shown previously that HGF-induced dissociation of MDCK epithelial cells is dependent on phosphatidylinositol 3-kinase (PI3K) activity (Potempa and Ridley, 1998). It was also suggested that whereas HGF-induced Ras activation increases Rac-GTP in a PI3K-dependent manner (Ridley et al, 1995;Scita et al, 1999;Royal et al, 2000;Zondag et al, 2000), RhoA might be activated through a PI3K-independent pathway (Zondag et al, 2000). In contrast to the latter report, we found that both RhoA ( Figure 7B) and Rac activation by HGF were strictly dependent on PI3K activity, being inhibited by treatment of the cultures with the PI3K inhibitor LY294002 (2 h, 20 M; Figure 7B).…”
Section: ⌬N-p120 Abrogates Activation Of Rhoa By Hgfmentioning
confidence: 97%
See 1 more Smart Citation
“…The association of Gab1 with the SHP-2 phosphatase is necessary for the sustained activation of MAPK required for branching morphogenesis (Maroun et al, 2000;Schaeper et al, 2000;Lamorte et al, 2002b). Met also activates pathways that modulate the actin cytoskeleton, cell adhesion and migration, including Src, Rho, Rac and PAK (Rahimi et al, 1998;Royal et al, 2000). The activation of some of these pathways is mediated through the interaction between Gab1 and Crk, whereby Crk can couple Gab1 to Rap1 and Rac (Lamorte et al, 2002a) and is required for the breakdown of cell-cell junctions and cell dispersal, in addition to branching morphogenesis in response to HGF/SF (Lamorte et al, 2002b;Rodrigues et al, 2005).…”
Section: Met Signal Transductionmentioning
confidence: 99%
“…Par exemple, l'activation des petites protéines G Ras, Rac et PAK (p21-activated kinase) contrôle le réarrangement du cytosquelette et la motilité [17]. La voie PI3K, via l'activation d'Akt (protéine kinase B), joue aussi un rôle central dans la survie cellulaire induite par Met [18], tout comme la régulation de p53 par Abl et p38 [19].…”
Section: Revuesunclassified